Comparison of shear bond strength and bonding time of a novel flash-free bonding system - Moon Young Lee; Georgios Kanavakis (2015)
To evaluate the bonding time, shear bond strength (SBS), and adhesive residue index (ARI) of APC(TM) Flash-Free bonding system.Thirty-six extracted human maxillary premolars were randomly divided into three groups (12 per group) and used for this in vitro study: group 1, APC Flash-Free Adhesive Coated Appliance System; group 2, Clarity ADVANCED Ceramic Bracket pasted manually; group 3 (control group), 3M APC PLUS Adhesive prepasted brackets bonded with the extruded flash removed. Bonding time was measured using a stopwatch. Bond strength was measured using an Instron at a cross-head speed of 1 mm/min. The ARI was graded on a scale from 1 to 5. Repeated-measures analysis of variance and post hoc Tukey tests were used for statistical analysis.It took significantly (P < .001) less time to bond in the APC Flash-Free Adhesive group (30.7 ± 3.3 seconds) compared with the control group (41.8 ± 4.0 seconds) and the manual group (39.2 ± 2.8 seconds). The APC Flash-Free Adhesive coated bracket had significantly (P < .001) greater SBS (13.7 ± 2.2 MPa) compared with the control group (10.8 ± 2.0 MPa) and the manual group (10.4 ± 1.4 MPa). The ARI was significantly (P < .001) greater with the APC Flash-Free Adhesive coated bracket compared with that of the other two groups.Compared with other methods of bonding, the APC Flash-Free Adhesive Coated System can potentially reduce bonding time while increasing SBS.